Colonial Corporate Social Responsibility: Company Healthcare in Java, East Sumatra and Belitung, 1910-1940 - Frank Ochsendorf (Universitas Gadjah Mada, 2018)
This article discusses the impact of investments by foreign firms in healthcare and hygienic measures on indigenous society in late-colonial Indonesia (1910-1940), focusing on three principal centers of foreign investment activity: Java, East Sumatra and the island of Belitung. Such facilities, although primarily intended for workers and their families, were sometimes accessible for members of indigenous society without contractual or family connection to the private company furnishing them. In rare cases, private companies invested directly in the welfare of local communities. The article concludes that the impact of the social investments on the state of health of indigenous communities was generally positive and a much-needed addition to scarcely available public healthcare. While such social investments can be regarded as examples of proto-corporate social responsibility strategies, the improvement of welfare was always a means through which the ultimate goal could be achieved: survival of the company and maximization of profits.